Physiological Changes in Ziziphus mauritiana by Different VAM Fungi - Mathur, Nishi; Vyas, Anil (Indian Forester, 1996)
Relative efficiency of seven VAM species G. fasciculatuun, G. mosseae, G. Constrictum. Scu. calsapoTa, Gig. Margarita, Acaul. Morrowae and Sele. Rubiformis, collected from rhizosphere soils of Z. mauritiana from arid and semi arid regions oflndia was tested. The investigation reveals that increasing amount of highly nutritious leaf fodder of Z. mauritiana can be produced by inoculating the plants with G. Fascicculatum as it increased the plant biomass and nutrient uptake most efficiently by colonizing the roots most effectively. However, field trails should be undertaken to assess the potentiality of this efficient strain.